2020
DOI: 10.1111/dme.14428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiles of post‐load glucose subgroups and their association with glycaemic traits over time: An IMI‐DIRECT study

Abstract: Aim To examine the hypothesis that, based on their glucose curves during a seven‐point oral glucose tolerance test, people at elevated type 2 diabetes risk can be divided into subgroups with different clinical profiles at baseline and different degrees of subsequent glycaemic deterioration. Methods We included 2126 participants at elevated type 2 diabetes risk from the Diabetes Research on Patient Stratification (IMI‐DIRECT) study. Latent class trajectory analysis was used to identify subgroups from a seven‐po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, we found that the classification based on the duration of diabetes alone cannot demonstrate a significant difference in either glycemic variability or prevalence of complications, although different β-cell function was observed. In previous studies, post-load glycemic patterns predicted the risk of type 2 diabetes 28 and adverse cardiovascular events 29 in non-diabetic patients, and some biochemical parameters differed significantly among non-diabetic patients 20 and newly diagnosed diabetic patients 30 . However, in this study, although the post-load glucose pattern was able to partially differentiate the glycemic status of patients, it was unable to detect differences in the prevalence of DR and atherosclerosis.…”
Section: Discussionmentioning
confidence: 86%
“…However, we found that the classification based on the duration of diabetes alone cannot demonstrate a significant difference in either glycemic variability or prevalence of complications, although different β-cell function was observed. In previous studies, post-load glycemic patterns predicted the risk of type 2 diabetes 28 and adverse cardiovascular events 29 in non-diabetic patients, and some biochemical parameters differed significantly among non-diabetic patients 20 and newly diagnosed diabetic patients 30 . However, in this study, although the post-load glucose pattern was able to partially differentiate the glycemic status of patients, it was unable to detect differences in the prevalence of DR and atherosclerosis.…”
Section: Discussionmentioning
confidence: 86%
“…To this end, a systematic assessment of patient reported outcomes measures (PROMs) has been shown to deliver information beyond routine examinations by physicians and to identify disabling deficits in every-day life after stroke [17,18]. A possible strategy towards understanding the development of different outcomes and towards risk stratification is classifying patients by the results of their outcomes and analyzing class characteristics, as shown for diabetes [24] and heart transplantation [20]. In mild to moderately affected stroke patients from an outpatient setting, a retrospective analysis showed promising results building distinct profiles or classes using the Patient-reported Outcomes Measurement Information System (PROMIS) [16].…”
Section: Introductionmentioning
confidence: 99%